METODE DAKWAH IMAM SHAFI’I DALAM ISTINBAT HUKUM ISLAM - Jawwas, Fahmi Ahmad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 10 No 1 (2014), 2016)
This paper discusses Shafi'i’s model of da’wah in the discovery of Islamic law. Al-Shafi'i is one of the da’wah leaders in Islamic law, so he was well known as a famous expert of Islamic law who taught the foundations of Islam and explained how to understand and teach the science of usul al-fiqh. To him, to learn the methodology of discovering Islamic law is necessary for a mujtahid who wants to learn in depth the rules of usul al-fiqh. The value of da’wah is very fundamental by which the Moslems are easily well- informed, and then implement Islamic law appropriately in their everyday life. Therefore, it is essential to learn and know Al-Shafi'i as a free legal expert (mujtahid mustaqil) and his school of Islamic law, which is also dominating in Indonesia